Kemampuan Peserta Didik dalam Membaca Lancar Level Dua Anak Kelas 2 Sekolah Dasar - Fania, Fania; Chairunnisa, Azizah; Chandra, Chandra; Wijanarko, Tiok (Lembaga Yasin AlSys, 2024)
This research aims to describe the ability to read fluently using pictorial media and determine the ability to read fluently in learning Indonesian using pictorial text media in class II elementary school students. The approach used in this research is qualitative with descriptive methods. The subject to support this research is one of the class II students at SD N in Pauh. Data collection techniques include observation and interviews. The results of the analysis of the ability of second grade elementary school students in reading fluently, it can be concluded that there are 2 aspects out of 4 aspects that are considered to be inappropriate.